Cytokines in equine platelet lysate and related blood products - Moellerberndt, Julia; Hagen, Alina; Niebert, Sabine; Büttner, Kathrin; Burk, Janina (Frontiers in Veterinary Science, 2023)
In equine medicine, the use of regenerative therapeutics has gained growing attention, but is still a new and complex field with room for improvement. Platelet lysate (PL) can be used as therapeutic agent but is also a promising supplement for the cultivation of multipotent mesenchymal stromal cells. To enable a targeted use of PL both in clinic and laboratory, it is crucial to learn more details on its effective ingredients. While so far, mainly growth factor components have been analyzed in platelet-based products such as PL, the current study focuses on the content of cytokines in serum, plasma, platelet concentrate and PL. Blood was harvested from 20 clinically healthy horses and subjected to blood count and chemistry analysis, as well as to further processing to PL. Plasma and platelet concentrate were produced by a buffy-coat-based method and PL was produced from the concentrate by freeze-thawing. Samples from each horse were analyzed regarding interleukin (IL)-1β, -4, -6 and -10, interferon-γ and tumor necrosis factor-α concentrations using sandwich ELISAs. Cytokine concentrations in serum, plasma, concentrate and PL were similar and correlated significantly. However, there was a large inter-individual variability in cytokine concentrations between the different donor horses. The samples from some donor animals had overall very high cytokine concentrations, while samples from other donors had no measurable cytokine ingredient. This pattern was observed for all cytokines. There was a noticeable link between high cytokine concentrations in the blood products and abnormal findings in blood chemistry. Cytokine concentrations in samples from horses with abnormal findings were significantly higher than in samples from the remaining horses. The interindividual differences in cytokine concentrations could be highly relevant when using PL for therapy and cell culture, as the mode of action of the PL is likely changed depending on the presence of pro- and anti-inflammatory cytokines. Blood chemistry might be useful to predict cytokine concentrations in blood products.